Assessment and optimization of Theileria parva sporozoite full-length p67 antigen expression in mammalian cells. - Giulia Tebaldi; Laura B Williams; Andrea E Verna; Francesca Macchi; Valentina Franceschi; Lindsay M Fry; Donald P Knowles; Gaetano Donofrio (Public Library of Science (PLoS), 2017)
Delivery of various forms of recombinant Theileria parva sporozoite antigen (p67) has been shown to elicit antibody responses in cattle capable of providing protection against East Coast fever, the clinical disease caused by T. parva. Previous formulations of full-length and shorter recombinant versions of p67 derived from bacteria, insect, and mammalian cell systems are expressed in non-native and highly unstable forms. The stable expression of full-length recombinant p67 in mammalian cells has never been described and has remained especially elusive. In this study, p67 was expressed in human-derived cells as a full-length, membrane-linked protein and as a secreted form by omission of the putative transmembrane domain. The recombinant protein expressed in this system yielded primarily two products based on Western immunoblot analysis, including one at the expected size of 67 kDa, and one with a higher than expected molecular weight. Through treatment with PNGase F, our data indicate that the larger product of this mammalian cell-expressed recombinant p67 cannot be attributed to glycosylation. By increasing the denaturing conditions, we determined that the larger sized mammalian cell-expressed recombinant p67 product is likely a dimeric aggregate of the protein. Both forms of this recombinant p67 reacted with a monoclonal antibody to the p67 molecule, which reacts with the native sporozoite. Additionally, through this work we developed multiple mammalian cell lines, including both human and bovine-derived cell lines, transduced by a lentiviral vector, that are constitutively able to express a stable, secreted form of p67 for use in immunization, diagnostics, or in vitro assays. The recombinant p67 developed in this system is immunogenic in goats and cattle based on ELISA and flow cytometric analysis. The development of a mammalian cell system that expresses full-length p67 in a stable form as described here is expected to optimize p67-based immunization.